Стежками декабристів м. Тульчина - Казьмирчук, Г.Д.; Казьмирчук, М.Г. (Сіверщина в історії України, 2020)
У статті пропонуються до розгляду маршрути пам’ятних місць
декабристів у місті Тульчині Вінницької області, висвітлюється історична пам’ять про них у житті вітчизняного суспільства, наголошується на доцільності збереження їхнього спадку для нащадків. The article proposes to consider the routes of the Decembrist sites in
the city of Tulchyn, Vinnytsia region, highlights the historical memory
of them in the life of the Ukrainian society, emphasizes the feasibility
of preserving their inheritance for posterity. One of the areas of study
and promotion of modern Decembrist science is local lore. At the present
stage, as the tourist industry grows, its functionaries want to know in
what state the monuments of one or another historical epoch have been
preserved. Existing local history literature does not always satisfy the
demand of sightseers, because new requests of society are much wider
and more extensive. The problem of tourism in places of the Decembrists
in Vinnytsia region has a solid domestic literature. Its appearance
is related to the scientific work of researchers of the 20–70’s of the
twentieth century. V. Bazylevych, D. Bahalii, L. Dobrovolskyi, M. Lysenko,
L. Medvedska, H. Serhienko considered the Decembrists’ stay in more
than 280 settlements of Ukraine, including in 30 cities and villages of
Vinnytsia. In 1980–1990 local subjects were covered by T. Podlasko,
D. Malakova, O. Kopayhorodska, M. Nedobii, A. Silkin, and Y. Latysh.
M. and H. Kazmirchuk also turned to this problem, having prepared a
series of brochures. Most of the material monuments of December’s time
are preserved, of course, in Tulchyn, where local authorities pay a lot of
attention to the preservation and restoration of these unique structures.
Among them, the Pestel House, the Decembrist ideologist and head of
the Southern Society, should be placed first. However, some Decembrist
sites have not survived to our time. Thus, the house of O.P. Yushnevskyi,
one of the directors of the Southern Society, whose photograph was in
the local history museum (we hope it has been preserved) was destroyed.
The memorial plaque from P.I. Pestel’s house has disappeared. Time
inexorably destroys the material values of the Decembrist era, we must
preserve them. This is our history and human memory of people who
wanted to improve the lives of our distant ancestors.